1980
DOI: 10.1021/jo01306a030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of phosphines having chiral organic groups ligated to chiral phosphorus

Abstract: 3691Dimethyl oxalate was also observed when the polar material obtained from the ozonolyiiis of 4 (14 mg) was treated in a similar fashion.Reduction of the Enamides 11 and 12 with Sodium Borohydride. To 2 mg of a 1:l mixture of l l and 12 dissolved in 15 mL of ethanol was added 100 mg of sodium borohydride. The solution was stirred at room temperature for 20 h. Excess reagent was destroyed with 1 N hydrochloric acid, and the solution was concentrated and extracted with dichloromethane. The dichloromethane laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 4 publications
(9 reference statements)
1
22
0
Order By: Relevance
“…Catalyst Me 3 SiBr or Me 3 SiI (20 %) was then added at room temperature by injection, and the mixture was heated at 80 8C for 5-12 h. The crude reaction mixture was allowed to cool to room temperature, and was either recrystallised or subjected to silica gel column chromatography or distillation under reduced pressure, yielding pure phosphine oxide (phosphinate or phosphonate). [26] (Table 1, [27] ( Table 1, [28] ( Table 1, P NMR date were consistent with those previously reported. [29] Allyl diphenyl phosphinoxide [30] ( Table 1, P NMR and 13 C NMR data were consistent with those previously reported.…”
Section: General Procedures For Phosphine Oxides (Phosphinates or Phossupporting
confidence: 90%
“…Catalyst Me 3 SiBr or Me 3 SiI (20 %) was then added at room temperature by injection, and the mixture was heated at 80 8C for 5-12 h. The crude reaction mixture was allowed to cool to room temperature, and was either recrystallised or subjected to silica gel column chromatography or distillation under reduced pressure, yielding pure phosphine oxide (phosphinate or phosphonate). [26] (Table 1, [27] ( Table 1, [28] ( Table 1, P NMR date were consistent with those previously reported. [29] Allyl diphenyl phosphinoxide [30] ( Table 1, P NMR and 13 C NMR data were consistent with those previously reported.…”
Section: General Procedures For Phosphine Oxides (Phosphinates or Phossupporting
confidence: 90%
“…The more expensive phenylsilane PhSiH 3 is a better reagent for reduction of phosphine oxides with retention at phosphorus (133) but also does not always give stereospecific reduction (188). Trichlorosilane has been used, but some phosphine oxides have been found to give racemic phosphine products.…”
Section: Phosphinate Ester Methodsmentioning
confidence: 99%
“…The corresponding neomenthyl phosphines 32 and 33 were prepared following Scheme 11 (49,188). An X-ray crystal- lographic structure determination on 31 allowed chemical correlation of all the structures, 30-33 (188). Both NMR studies (204) and conformational studies (205) have also been reported for menthyl-and neomenthylmethylphenylphosphines.…”
Section: + 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Two categories of reducing agents have been exploited for use in such stereospecific reductions. Several silanes have been used for reduction of the tetracoordinated phosphine chalcogenides [35][36][37][38][39][40][41][42], and lithium aluminum hydride has been used for the reduction of phosphine chalcogenides [43][44][45], as shown in Scheme (2), as well as the cleavage of a benzyl group from quaternary phosphonium salts [23][24][25][26][27][28][29][30][31][32][33][34], shown in Scheme (3).…”
Section: Tricoordinated Phosphorusmentioning
confidence: 99%